Pengaruh Marinasi Berbagai Konsentrasi Sari Jeruk Nipis (Citrus aurantifolia) terhadap Sifat Fisik (pH, Keempukan, Daya Ikat Air, dan Susut Masak) Daging Kerbau Beku - Yasmin, Adinda Putri; Pratama, Andry; Suryaningsih, Lilis (Jurnal Teknologi Hasil Peternakan, 2023)
Marination is the process of soaking meat in the marinade to increase meat retention, improve flavour, increase fatness, juiceness, and water hold capacity, decrease cooking loss, and extend meat tenderness. In the process of marinating, lime that contained citric acid help to break down proteins so that the meat became more tender. This study aims to determine the effect of marinating various concentrations of lime juice (Citrus aurantifolia) on the physical properties (pH, tenderness, water holding capacity, and cooking loss) of frozen buffalo meat and determined which lime juice (Citrus aurantifolia) concentration that can produce better physical properties of frozen buffalo meat. The study had experimentally based on the Complete Randomized Design (CRD) with 5 lime juice concentration, namely P0 (0%), P1 (10%), P2 (20%), P3 (30%), and P4 (40%), with a repeat of 4 times. The data obtained were analyzed by Analysis of Variance (ANOVA) and if there was a significance difference Duncan’s further test is carried out. The results showed that marination using the various concentrations of lime juice has affected on the pH and tenderness of buffalo meat, but the water holding capacity and cooking loss were not affected. The result showed that the used of concentration 20% can provide better quality of physical properties of frozen buffalo meat with pH content 5,3 and 51,05 mm/g/10s tenderness content.